O rio que corre pela aldeia: relações estabelecidas por torcedores comuns de Belo Horizonte com o torcer, com a violência e com o novo estádio Independência - Marcos de Abreu Melo (2013)
The present dissertation was highly concerned about how ordinary football supporters from Belo Horizonte behave within the supporting atmosphere felt during matches at the recently-inaugurated Stadium Raimundo Sampaio (Independência), in the capital of Minas Gerais. The documentary and field research developed can also be characterized as descriptive, displaying both quantitative and qualitative features. The stadium was visited nine times in 2012 when América Futebol Clube, Clube Atlético Mineiro and Cruzeiro Esporte Clube were playing as hosts. Such visitations were carried out during the second season of the Brazilian National Championship in both Premier and Second leagues. Field registers were recorded before, during and after the matches, and 231 football supporters filled in questionnaires. Afterwards, five supporters from the previous sample were selected to answer semi-structured interviews. The data were collected and analyzed considering three main foci: the relationship between the supporters and their supporting feeling and football club; the relationship between the supporters and the stadium; and the relationship between the supporters and the violence. It was possible to notice differences and similarities among the supporters beliefs from each of the football clubs investigated in this research. The data indicate that América supporters are very proud of Independência, the majority of them despise bad language and songs in the stadiums, and they do not have a great rival in order to reaffirm their sense of belonging to a football club. Supporters from Atlético, on their turn, see in their own supporting group one of the greatest reasons for supporting the team. They embrace Independência as the stadium for Atléticos matches and buy tickets on the black market. Cruzeiro supporters, on the other hand, have no sense of belonging to Independência. They rely greatly on previously-won championships and cups in order to reinforce their feeling of belonging. Their five-star symbol, in addition, is very important for Cruzeiro. Nevertheless, the supporters from all three teams approved Independência being rebuilt and the Military Police Force presence during the matches, although they felt a lack of safety mainly around the stadium area. The stadiums location and newness pleased the supporters, even though its parking lot and the match visibility from the grandstand were regarded as negative aspects of the new Independência. The data analysis not only allowed to observe the ebb and flow of the act of supporting in the capital of Minas Gerais but also highlighted advances and tensions in the modernization process of football stadiums